NURSING CARE ACCOUNTABILITY - Hidayah, Nur (Journal of Islam and Science, 2014)
Nursing science is based on a very broad theory. Nursing process is the method by which a concept is applied in nursing practice. It can be termed as an approach to solving the problem (problem- solving) that requires knowledge, techniques, and skills interpersonel which aim to meet the need of clients, families, and communities. The nursing process consists of five interconnected sequential stages, namely the assessment, diagnosis, planning, implementation, and evaluation. The stages of the intellectual functions integrate problem-solving in a nursing define. Nursing process in general purpose is to rearrange the framework concept based on individual circumstances (client), families, and communities so that their needs can be fulfilled. Accountability (accountability) is accountable for behavior and its results are included in the scope of one's professional role as reflected in the periodic report in writing on the attitude and results. Nurses accountable to themselves, patients, profession, fellow employees and the society.